2020
DOI: 10.1002/asna.202023778
|View full text |Cite
|
Sign up to set email alerts
|

Charge exchange, from the sky to the laboratory: A method to determine state‐selective cross‐sections for improved modeling

Abstract: Charge exchange (CX) is a semi‐resonant recombination process that can lead to spectral line emission in the X‐ray band. It occurs in nearly any environment where hot plasma and cold gas interact: in the solar system, in comets and planetary atmospheres, and likely astrophysically, in, for example, supernova remnants and galaxy clusters. It also contributes to the soft X‐ray background. Accurate spectral modeling of CX is thus critical to properly interpreting our astrophysical observations, but the commonly u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, these theoretical models have been sparsely tested (Lyons et al 2017;Liu et al 2022). Other simpler approaches include the scaling law for n capture (Janev & Winter 1985;Otranto et al 2006) and the analytical l distributions for approximating the lstate population (Janev & Winter 1985;Smith et al 2014), adopted in MCLZ for initial bare ions (Cumbee et al 2016;Lyons et al 2017;Betancourt-Martinez et al 2020). Recently, Mullen et al (2016) found that these l distributions struggle to accurately reflect the true l population for high-n capture (e.g., n ∼12-14), and proposed the shifted low-energy (SL1) distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, these theoretical models have been sparsely tested (Lyons et al 2017;Liu et al 2022). Other simpler approaches include the scaling law for n capture (Janev & Winter 1985;Otranto et al 2006) and the analytical l distributions for approximating the lstate population (Janev & Winter 1985;Smith et al 2014), adopted in MCLZ for initial bare ions (Cumbee et al 2016;Lyons et al 2017;Betancourt-Martinez et al 2020). Recently, Mullen et al (2016) found that these l distributions struggle to accurately reflect the true l population for high-n capture (e.g., n ∼12-14), and proposed the shifted low-energy (SL1) distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral measurements of these collision systems at solar wind velocities with microcalorimeters (spectral resolution <10 eV) would be capable of measuring both individual Lyman ratios and the hardness ratio as a function of collision energy. Alternatively, the ℓ distribution of capture states could be extracted directly from high-resolution spectra using the methods developed and described by Betancourt-Martinez et al (2020), and would provide an invaluable benchmark of analytic ℓ distributions.…”
Section: Discussionmentioning
confidence: 99%
“…3(C)). The rate of error between the two images was calculated by the role mean square error (MSE) [12][13][14][15][16][17][18][19][20] using Eq. ( 1): ∑ where is the original image and is the image after coloring, where the error was 9%.…”
Section: The Work Of Colorationmentioning
confidence: 99%